Skyward ebook - Sanderson, Brandon (Skyward, 2018)
A NEW YORK TIMES BESTSELLER! From Brandon Sanderson, the #1 New York Times bestselling author of the Reckoners series, Words of Radiance, and the internationally bestselling Mistborn series, comes the first book in an epic new series about a girl who dreams of becoming a pilot in a dangerous world at war for humanity's future. Spensa's world has been under attack for decades. Now pilots are the heroes of what's left of the human race, and becoming one has always been Spensa's dream. Since she was a little girl, she has imagined soaring skyward and proving her bravery. But her fate is intertwined with her father's—a pilot himself who was killed years ago when he abruptly deserted his team, leaving Spensa's chances of attending flight school at slim to none. No one will let Spensa forget what her father did, yet fate works in mysterious ways. Flight school might be a long shot, but she is determined to fly. And an accidental discovery in a long-forgotten cavern might just provide her with a way to claim the stars. Praise for Skyward : A Kirkus Reviews Best Book of the Year " Startling revelations and stakes-raising implications ...Sanderson plainly had a ball with this nonstop, highflying opener, and readers will too. "—Kirkus Reviews , Starred Review "With this action-packed trilogy opener , Sanderson offers up a resourceful, fearless heroine and a memorable cast ...[and] as the pulse-pounding story intensifies and reveals its secrets, a cliffhanger ending sets things up for the next installment." —Publishers Weekly , Starred Review "It is impossible to turn the pages fast enough. "— Booklist " Sanderson delivers a cinematic adventure that explores the defining aspects of the individual versus the society...[and] fans of [his] will not be disappointed. " —SLJ Praise for Brandon Sanderson's Reckoners series: #1 New York Times Bestselling Series " Another win for Sanderson . . . he's simply a brilliant writer. Period."—Patrick Rothfuss, author of the New York Times and USA Today bestseller The Name of the Wind "Action-packed." — EW " Compelling. . . . Sanderson uses plot twists that he teases enough for readers to pick up on to distract from the more dramatic reveals he has in store."—AV Club